THE NOTION SPEECH ACTS AND ANALYSES OF THE WORK “A CUP OF TEA” BY KATHERINE MANSFIELD - Khamrakulova Ravshanoy Abdulakhatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with clarifying the meaning and differences of speech acts through analysis of the story written by Katherine Mansfield